Diversidade genética e reação de linhagens de feijoeiro inoculadas com mistura de raças de Pseudocercospora griseola em diferentes estádios e ambientes - Pereira, Rafael (2017)
Objectives of this research were: evaluate genetic diversity in different common bean lines; evaluate and compare different phenotyping methodologies of angular leaf spot severity in common bean for use in breeding programs; verify the efficiency of mixture of Pseudocercospora griseola strains to evaluate disease severity by comparing aggressiveness among strains/mixture. In genetic diversity analyis of 149 common bean lines, 18 polymorphic microsatellite markers distributed in nine common bean chromosomes were used. One hundred and twenty seven alleles were identified, with average of 7.47 alleles per locus and average diversity among loci of 0.55. Estimates of genetic similarities ranged of 0 to 0.96. Using an approach to infer genetic population structure, common bean lines were separated into seven groups (K = 7). SSR markers used were useful to estimate genetic parameters in common bean germplasm, as well as to separate bean lines evaluated in groups of greater genetic similarity. To comparing different phenotyping strategies, 144 common bean lines were evaluated to reaction to P. griseola in greenhouse (inoculation in V2 and V3 stages) and in field. Percentage of resistant lines considering phenotyping at V2 stage, V3 stage and in field was 31%, 7% and 10%, respectively. Estimates of coincidence indices between field and greenhouse evaluations were 68%, 69% and 88% in V2-V3, V2-field and V3-field, respectively. Joint analysis using mixed model approach was promising to identify resistant genotypes in different environments/evaluation stages. Resistant genotypes were those with highest level of resistance in average of environments/evaluation stages. Comparison between individual strains and strains mixture was carried out by assessment of disease severity using a score scale and percentage of leaf area with symptoms (%LAS). Experiments were carried out in greenhouse, using three strains and respective mixture, inoculated in six common bean lines. In comparison of strains and mixture, it was verified that score scale was more efficient than %LAS to distinguish aggressiveness, being therefore, the most indicated method to evaluate angular leaf spot severity in common bean. Mixture of P. griseola races was efficient to evaluate angular leaf spot severity in common bean, presenting greater aggressiveness compared with the individually races inoculated.